Circulating soluble CD36 as a novel biomarker for progression and prognosis of HBV-related liver diseases - Cai, Chunxian; Xiao, Anhua; Luo, Xiaoqing; Zheng, Enze; Li, Yiyu; Lei, Yu; Zhong, Shan; Chen, Yaxi; Yang, Ping; Tang, Zhurong; Zhou, Zhi (Frontiers in Microbiology, 2022)
Background: Our previous study suggested CD36 may be a positive regulator of hepatitis B virus (HBV) replication in vitro. Therefore, the present study aimed to investigate whether circulating soluble CD36 (sCD36) could serve as a diagnostic and prognostic biomarker for HBV-related liver diseases based on the clinic collected data. Methods: A total of 282 subjects were divided into healthy controls (HC, n=47), chronic hepatitis B (CHB, n=68), HBV-related liver cirrhosis (HBV-LC, n=167). Soluble CD36 in plasma was measured by ELISA, and monocyte or platelet CD36 expression was determined by flow cytometry. Results: There was a step-wise increase of sCD36 with the progression of chronic HBV infection, and it was the highest in the HBV- LC group with liver failure (1.50, IQR:1.04-2.00) as compared with HC (0.38, IQR:0.27-0.38), CHB (0.75, IQR:0.40-1.13), and HBV-LC without liver failure (1.02, IQR:0.61-1.35) group. Circulating sCD36 was not correlated with serum HBV DNA levels, but correlated with liver function parameters. Additionally, ROC analysis confirmed sCD36 could be used to predict liver failure for HBV- LC patients, which yielded an AUC of 0.775 with 71.0% sensitivity and 72.2% specificity. Multivariate logistic regression analysis revealed sCD36 is an independent risk factor in predicting liver failure. Moreover, plasma or circulating sCD36 in HBV-LC patients was significantly correlated with prognostic indices, including MELD, MELD-Na and CHILD-PUGH scores. On the other hand, CD36 expression on monocytes or platelets was positively correlated with plasma sCD36 levels, whereas they were not strongly associated with the disease severity. Conclusions: Circulating sCD36 could be used as a novel noninvasive biomarker for predicting liver failure and prognosis in chronic HBV infected patients.